Diurnal Variation in Nonstructural Carbohydrate Storage in Trees: Remobilization and Vertical Mixing - Tixier, Aude (Plant Physiol, 2018)
Nonstructural carbohydrate (NSC) storage plays a critical role in tree function and survival, but understanding and predicting local NSC storage dynamics is challenging because NSC storage pools are dispersed throughout the complex architecture of trees and continuously exchange carbon between source and sink organs at different time scales. To address these knowledge gaps, characterization and understanding of NSC diel variation are necessary. Here, we analyzed diurnal NSC dynamics in the overall architecture of almond (Prunus dulcis) trees. We also analyzed the allocation of newly assimilated carbon using isotopic labeling. We show that both components of NSC (i.e. soluble carbohydrates and starch) are highly dynamic at the diurnal time scale and that these trends are influenced by tissue type, age, and/or position within the canopy. In leaves, starch reserves can be depleted completely during the night, while woody tissue starch levels may vary by more than 50% over a daily cycle. Recently assimilated carbon showed a dispersed downward allocation across the entire tree. NSC diurnal fluctuations within the tree’s structure in combination with dispersed carbon allocation patterns provide evidence for the presence of vertical mixing and suggest that the xylem acts as a secondary NSC redistribution pathway.